The Sound Effect in the Discourse of the Angels (peace be upon them) Selected models from the Holy Qur’an) - Ragab, Hammam; Ghani, Mona (Islamic Sciences Journal, 2023)
The study is conducted to clarify the sound effect and its flow within the linguistic text and to give its phonetic value to the determinants of the text and raise the meaning towards the recipients. It gives an extension of it in its area in which it is established within the context, and what is associated with it from the indication of the director and the characteristic that exemplifies that wave spectrum and from the linguistic studies that have emerged. The studies are concerned with the conditions of the interlocutors and the signs and motives of the discourse, and what is obtained from the rhetorical process and standing on the most important elements on which it is based the discourse between the interlocutors (the sender + the message + the recipient) and how to direct the speech in a way that its intent is understandable to the recipient, so the speech of the angels (peace be upon them) is the focus of the research and its main foundations.